2021
DOI: 10.1002/ptr.7194
|View full text |Cite
|
Sign up to set email alerts
|

Targeting interleukin‐β by plant‐derived natural products: Implications for the treatment of atherosclerotic cardiovascular disease

Abstract: Inflammation is the main contributing factor to atheroma formation in atherosclerosis. Interleukin‐1 beta (IL‐1β) is an inflammatory mediator found in endothelial cells and resident leukocytes. Canakinumab is a selective monoclonal antibody against IL‐1β which attenuates inflammation and concurrently precipitates fatal infections and sepsis. Natural products derived from medicinal plants, herbal remedy and functional foods are widely used nowadays. Experimental and clinical trial evidence supports that some na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 240 publications
0
11
0
Order By: Relevance
“…Anti‐oxidative strategies are, therefore, helpful in preventing atherosclerosis by inhibiting oxidative stress and inflammation 60 . In this regard, Vahdat‐Lasemi et al found that 6‐gingerol may have a therapeutic potential in treating arteriosclerosis by reducing inflammation and decreasing IL‐1 β expression as an essential inflammatory mediator that is mainly produced by endothelial cells and resident leukocytes 61–64 . As inflammation is also responsible for atherosclerosis, reducing the expression of inflammatory mediators may help treat the disease 61–64 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti‐oxidative strategies are, therefore, helpful in preventing atherosclerosis by inhibiting oxidative stress and inflammation 60 . In this regard, Vahdat‐Lasemi et al found that 6‐gingerol may have a therapeutic potential in treating arteriosclerosis by reducing inflammation and decreasing IL‐1 β expression as an essential inflammatory mediator that is mainly produced by endothelial cells and resident leukocytes 61–64 . As inflammation is also responsible for atherosclerosis, reducing the expression of inflammatory mediators may help treat the disease 61–64 .…”
Section: Resultsmentioning
confidence: 99%
“…[61][62][63][64] As inflammation is also responsible for atherosclerosis, reducing the expression of inflammatory mediators may help treat the disease. [61][62][63][64] Furthermore, 6-gingerol has decreased the levels of IL-1β, lipids, inflammatory factors, and atheroma growth. 33,64 In addition to its role in energy homeostasis and atherosclerosis, several studies indicated that AMPK plays a vital role in inflammation.…”
Section: Anti-atherosclerosis Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them affect production of different components of immune system thus modulating numerous immune reactions, but also other physiological processes, through various signaling pathways ( 123 , 124 ). For instance, quercetin showed inhibitory effect on production of complement components ( 125 , 126 ), interleukins ( 127 , 128 ), and immunoglobulins ( 125 , 129 ). However, these effects should be considered with special attention when the use of flavonoids by athletes is reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several phytopharmaceuticals have been shown to be nontoxic, clinically and pharmacologically safe, and suitable for screening as potential therapeutic metabolites [ 31 ]. In a phase I clinical trial, of patients with high-risk or pre-malignant lesions with the chemopreventive agent curcumin [ 32 ] , it was found to be very potent in anti-inflammatory effects in many chronic diseases by promoting modulation of various signaling pathways and cellular mechanisms associated with inflammation, degradation, and apoptosis [ 15 , 33 , 34 , 35 , 36 ], including different types of cancer [ 37 , 38 , 39 , 40 ], neuro-inflammatory disorders [ 41 , 42 , 43 ], chronic destructive pulmonary disease (COPD) [ 44 , 45 , 46 , 47 ], psoriasis [ 48 , 49 , 50 ], cardio-vascular disease [ 51 , 52 , 53 ], and many more. In addition, natural products showed to have a restorative effect on skeletal disorders, such as osteoarthritis (OA), osteoporosis, intervertebral disc disease, and rheumatoid arthritis (RA), while representing a safe treatment method [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%